Determinants of Experiential Marketing on the Intention to Use Outpatient Services in Class C Hospital - Lucki Lucki; MF. Arrozi Adhikara; Rokiah Kusumapradja (International Forum of Researchers and Lecturers, 2025)
Introduction: Experiential marketing has become a growing trend in promotional activities by emphasizing personalization and active customer involvement. Preliminary observations indicate a decline in outpatient visits among patients with general insurance and non-JKN coverage in 2023, which may be influenced by a decrease in their intention to use outpatient services. This condition highlights the need for hospitals to implement experiential marketing strategies to enhance patient interest and experience. Objective: This study aims to empirically examine the influence of patient experience and service perception on the intention to use outpatient services, with Strategic Experiential Modules (SEMs) as an intervening variable. Methods: This quantitative research employs a causal design involving outpatient service users as the population. A non-probability sampling technique was used, yielding 249 respondents. Data were collected using a questionnaire and analyzed using Structural Equation Modeling (SEM) with AMOS software. Results: The findings reveal that patient experience and service perception simultaneously have a significant positive influence on the intention to use outpatient services through SEMs. Service perception directly shows a significant positive effect on both SEMs and intention to use outpatient services, while SEMs also significantly enhance usage intention. Service perception emerges as the dominant variable in increasing SEMs and usage intention, whereas patient experience has the weakest effect. Conclusion: Patient experience and service perception collectively influence the intention to use outpatient services with SEMs as an intervening variable. Strengthening Customer Relationship Management is essential by improving human resources and optimizing service asset.